The Influence of Corporate Entrepreneurship on Innovation Performance through Employee Engagement at Latimo Gelato - Wydiani, Astarina Yulinda (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to examine the effect of corporate entrepreneurship on innovation performance with employee engagement as a mediating variable. This study uses a quantitative method using SmartPLS to process data. The number of respondents in this study was 35 Latimo Gelato employees who were determined using the non-probability sampling method, namely saturated sampling. The data in this study were collected using a questionnaire which was distributed directly to each respondent. The results showed that corporate entrepreneurship had a significant positive effect on innovation performance, corporate entrepreneurship had a significant positive effect on employee engagement, and employee engagement had a significant positive effect on innovation performance.